Disclosure of Corporate Social Responsibility (CSR): Legitimacy Theory Perspective - Ayu Septiana, Vidya; Aminah, Aminah (LPPPIPublishing, 2025)
This study is to analyze the effect of profitability, independent board of commissioners, and audit committee on the implementation of corporate social responsibility (CSR). This study uses panel data obtained from 20 companies over a three-year period (2021–2023) resulting in 60 observations. A quantitative approach with multiple linear regression analysis is used to evaluate the relationship between variables. The independent variables include profitability, independent board of commissioners, and audit committee, while CSR is the dependent variable. The results of the study indicate that there is a significant positive effect between the Audit Committee on CSR, while there is a significant negative effect between Profitability and CSR. On the other hand, the Audit Committee Board has no significant effect on CSR.